Pendeteksian dan Pencegahan Kekerasan terhadap Anak Sekolah Dasar - Raja Al Fath Widya Iswara (Jurnal SOLMA, 2021)
Background: Violence against children (KtA) is acts of physical, sexual, emotional abuse, or neglect of children. KtA is a complex problem and has a varied clinical spectrum, which will have an impact on the growth and development of children. Data from KPAI shows that the number of cases of violence against children in Indonesia has increased significantly every year at school age. This community service aims to detect current and past violence and prevent violence against elementary school children, especially in Lalolara Village, Kambu District, Kendari City. Method: A descriptive qualitative with techniques used in the form of anamnesis, physical examination and drug testing to detect violence against children and socialization of prevention of violence against elementary school children. Result: This service obtained 96 students, signs of violence currently 0 people (0%), a history of violence previously experienced as many as 39 people consisting of a history of physical violence 36 people (92.31%), 2 people (2.13%) and psychological violence. sexual violence 1 person (2.56%). Preventive action is carried out by socializing to children (students) and elementary school teachers in Lalolara village, Kambu sub-district, Kendari city. Extension materials include actions that are useful in recognizing the characteristics, impacts, and prevention of violence against children (KtA). Conclusions: From this dedication is that there are no signs of physical violence or drug use in children at this time, but most children have a history of physical abuse by their parents.